Perspektif Positif: Dinamika Perilaku Hegemoni Dalam Budaya Kerja Pegawai - Zakiya, Arifatuz; Jainudin; Astuti, Fidia (Happiness: Journal of Psychology and Islamic Science, 2023)
Social interactions in the workplace play a pivotal role in shaping the work culture and influencing organizational productivity and success. Particularly, the relationship between superiors and subordinates holds the potential for creating hegemonic behaviors, where superiors utilize their experience and knowledge to influence subordinates. This research aims to delve deeper into the processes, forms, levels, and impacts of hegemonic behaviors within the work culture of employees at the Department X in Kediri District, with a focus on the positive perspective of Antonio Gramsci's theory. This study adopts a qualitative approach and a case study research design. Information is obtained from two informants, a superior and a subordinate, through interviews and observations. Data is analyzed through method triangulation, involving raw data collection, data reduction, data interpretation, data analysis, and drawing conclusions. The research findings indicate that hegemonic behavior evolves through the demonstration of intellectual and moral leadership by superiors, subsequently gaining the approval of subordinates regarding the dominance of superiors. Forms of hegemonic behavior encompass aspects of intellectual and moral leadership, approval, and domination. The identified level of hegemony suggests a "declining hegemony." The impact of hegemonic behavior includes positive changes in work processes, ethics, communication, and power utilization. This study reinforces the understanding of the dynamics of relationships between superiors and subordinates in the workplace and their implications for work culture. It also provides a foundation for improving the work environment and fostering more harmonious inter-employee relationships.